From Possibility To Reality: The Vajdaság Economic Development Program In The Service Of Rural Developement - Juhász, Bálint (Észak-magyarországi Stratégiai Füzetek, 2023)
Abstract: As a national political goal, the prosperity of the Hungarian communities living as a minority in their homeland, i.e., in areas beyond the borders of the motherland is as old as the greatest tragedy in the history of the Hungarian nation, the division of the country caused by the peace decree ending the Great War, as a result of which Hungary lost two-thirds of its territory and one-third of its population. The unique contribution of this study lies in the fact that it approaches ‘homeland prosperity’ not from the point of view of the territory of current Hungary, but, in fact, from without the borders, considering homeland as the territories where Hungarians live within the borders of another state. The Territorial and Economic Development Strategy and Action Plan of the Hungarian Communities of Vajdaság was formulated with the participation of nearly 30 experts, starting 2012 and eventually completed in 2015. In 2016, the Hungarian government launched an economic development program in the Carpathian Basin for the prosperity of fellow countrymen. The Vajdaság Economic Development Program (VEDP) is currently Hungary's largest cross-border economic development program, a pioneer in the field of implementing economic development programs abroad; it serves as a model for similar actions abroad. During its 7.5-year existence, to date, the Prosperitati Foundation has published 55 calls for tenders in 10 tender rounds in the fields of agriculture, tourism, village house purchase and business development. Summing up the figures of small, medium and highvalue projects, the total value of the projects so far is more than HUF 177.43 billion (RSD 61.71 billion, €526.16 million). The value of the awarded non-refundable aid is nearly HUF 83.16 billion (RSD 29.14 billion, €248.4 million). The purpose of the study is to examine the ability of municipalities in Vajdaság to raise funds, with particular regard to the proportion of the population of the Hungarian community.